PENGEMBANGAN E-LEARNING BERBASIS WEBSITE MENGGUNAKAN MOODLE PADA SMA NEGERI 1 JONGGOL - Amir Syarifudin (2021)
The development of highly advanced information technology today requires students and teachers to be technology literate in the learning process. The increasing need for information technology in the 2013 Curriculum, which states that teachers are expected to be literate or understand information, media and information and communication technology. Learning media that already use technology such as e-learning can enable students to adapt to current technological developments. E-Learning is also a solution to solving learning problems that arise due to limited time, space, and the number of meetings between students and teachers at SMA Negeri 1 Jonggol. Based on these limitations, a Website-Based E-Learning Application was built using an LMS (Learning Management System), namely Moodle. The application of E-Learning with LMS was developed using the PHP programming language and MySQL database as well as using the Research and Development (R & D) method in order to produce a particular product, and to test the effectiveness of the product. With the final result or the expected output from this research, namely the website-based E-Learning application using Moodle and the E-Learning Handbook for admins, teachers, and students.